Narrative Text Analysis on the 4th Grade Elementary School’s 2013 Curriculum Instructional Materials in Gender Identity Perspective - Permata, Gitta Bella; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research motivated by the lowness of gender equality and equity in Indonesia. It can be seen from the Global Gender Gap Report, World Economic Forum 2020 which ranked Indonesia at 85th from 153 countries. Meanwhile, gender equality is one of the 17 goals of SDGs (Sustainable Development Goals). This research aim to analyze narrative text on the 4th grade elementary school’s 2013 curriculum instructional materials in gender identity perspective. The method used in this research was content analysis and the objects of this research were suggestive narrative texts on the 4th grade elementary school’s student books, 1st and 2nd semester 2013 curriculum published by The Ministry of Education and Culture 2017 revised edition. The texts focused on short stories, legends, and fairy tale. Based on data analysis, narrative text on the 4th grade elementary school’s 2013 curriculum instructional materials contains three forms of gender identity that reflected in the text. The three forms of gender identity were 48 sentences as feminine on women, 51 sentences as masculine on men, and 64 sentences as androgynous (47 sentences for feminine on men and 17 sentences for masculine on women). On the instructional materials, it was found that masculine characteristics are still predominantly visualized on men, while feminine characteristics in both women and men are already balanced.